2016
DOI: 10.1093/infdis/jiw600
|View full text |Cite
|
Sign up to set email alerts
|

HPV-6 molecular variants association with the development of genital warts in men: The HIM Study

Abstract: HPV-6 B1 variants are more prevalent in genital swabs that precede GW development, and confer an increased risk for GW. Further research is warranted to understand the possible involvement of B1 variants in the progression to clinically relevant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…Concerning HLA‐DQB1*03:01 allele, identified as a risk factor for OLI, previous studies showed conflicting results: Whereas in chronic hepatitis, this allele has been correlated in some instances with HCV clearance (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ), other authors have reported a link between HLA‐DQB1*03:01 and HPV6 infection (Chen et al ., ). Notably, this HPV subtype, despite being considered as low risk for cervical cancer, is established to cause genital lesions and to be found in the semen (Lyu et al ., ; Flores‐Díaz et al ., ). In our cohort, no association of HLA‐DQB1*03:01 with HPV was not detected.…”
Section: Discussionmentioning
confidence: 97%
“…Concerning HLA‐DQB1*03:01 allele, identified as a risk factor for OLI, previous studies showed conflicting results: Whereas in chronic hepatitis, this allele has been correlated in some instances with HCV clearance (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ), other authors have reported a link between HLA‐DQB1*03:01 and HPV6 infection (Chen et al ., ). Notably, this HPV subtype, despite being considered as low risk for cervical cancer, is established to cause genital lesions and to be found in the semen (Lyu et al ., ; Flores‐Díaz et al ., ). In our cohort, no association of HLA‐DQB1*03:01 with HPV was not detected.…”
Section: Discussionmentioning
confidence: 97%
“…The median time to GW detection was 17.1 months; however, it was shortest among men with HPV types 6 or 11 infections (median of 7.7 months). Interestingly, while HPV-6 nucleotide variability was associated with GW development [73], there was a lack of association between any particular HPV-11 variant and increased risk of GW [74]. Recent sexual behavior was strongly associated with GW incidence, whereas frequent condom use was protective [15].…”
Section: Hpv Genital Infection and Associated Diseases: The Him Studymentioning
confidence: 99%
“…DNA from HPV 6-and HPV 11-positive cervical swabs were submitted to PCR for amplification of a fragment of the L2 and E2/NCR2 regions, respectively (4,5). Reaction products were sequenced in an ABI PRISM 3130XL GeneticAnalyzer (Applied Biosystems) using the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems).…”
Section: Characterization Of Hpv Variantsmentioning
confidence: 99%